Effect of iron supplementation on the modulation of iron metabolism, muscle damage biomarkers and cortisol in professional cyclists - Córdova, A.; Mielgo-Ayuso, J.; Fernandez-Lazaro, C. I.; Caballero-Garcia, A.; Roche, E.; Fernández-Lázaro, D. (Nutrients, 2019)
Background: The intense efforts made during 3-week stage races may reduce iron metabolism and hematological parameters. These efforts may increase the levels of circulating muscle damage markers and some hormones. All of these physiological changes may have negative consequences not only for the performance of athletes but also for their health. The main aim of this study was to evaluate the effects of supplementation with 80 mg/day of iron on haematological parameters, serum cortisol and biochemical muscle indicators on elite male cyclists during the 3-week stage race the Vuelta a España. Our secondary aim was to examine whether the hematological profile is associated with muscular damage parameters and cortisol. Methods: Eighteen elite male cyclists from two teams were randomly assigned to one of two groups: (1) control group (CG, n = 9; age: 26.1 ± 4.6 years; maximum oxygen uptake per kg: 78.0 ± 5.4 mL/kg/min) or (2) group treated with 80 mg/day iron (800 mg of iron protein succinylate, ITG, n = 9; age: 25.7 ± 6.4 years; maximum oxygen uptake per kg: 77.6 ± 6.5 mL/kg/min). The cyclists were subjected to blood tests one week before the start of the race (T1) and after 4 weeks of treatment, coinciding with the end of the competition (T2). Iron metabolism parameters, muscle damage indicators and serum cortisol were assessed. Repeated-measures ANOVA with group as a factor (GC and ITG) were used to examine the differences between groups throughout the study (time × group) after iron supplementation treatment. Results: Significant differences were observed between groups throughout the study in the group-by-time interaction and changes in serum iron (GC: -8.93 ± 10.35% vs. ITG: 0.60 ± 8.64%; p = 0.018), ferritin (GC: -13.88 ± 23.53% vs. ITG: 91.08 ± 118.30%; p = 0.004), haemoglobin (GC: 10.00 ± 3.32% vs. ITG: 13.04 ± 5.64%; p < 0.001), haematocrit (GC: -1.17 ± 3.78% vs. ITG: 7.32 ± 3.92%; p < 0.001) and cortisol (GC: 24.74 ± 25.84% vs. ITG: -13.54 ± 13.61%; p = 0.005). However, no significant group-by-time interaction was observed for the circulating muscle biomarkers. Additionally, significant negative correlations of serum iron, haemoglobin and haematocrit with muscle circulating biomarkers and cortisol (p < 0.05) were observed. Conclusions: Oral iron supplementation with 80 mg/day iron (800 mg of iron protein succinylate) effectively prevented a decline in haematological parameters (serum iron, ferritin, haemoglobin and haematocrit) and maintained optimal levels of recovery in elite cyclists during the Vuelta a España. Moreover, the hematological values were shown to have relationship with muscular recovery parameters.